2018
DOI: 10.1097/acm.0000000000002342
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Models for Career Advancement Sponsorship in Academic Medicine: The Time Is Here; the Time Is Now

Abstract: The business community has honed the concept of sponsorship and promulgated its utility for harnessing the talent of high-performing women and minorities whose contributions often go unrecognized within organizations. In recent years, academic medicine has begun to do the same. Whereas mentorship often centers on personal and professional development (e.g., skill building and goal setting), sponsorship focuses on enhancing the visibility, credibility, and professional networks of talented individuals. For upwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 14 publications
0
70
0
1
Order By: Relevance
“…Thus men, who occupy the majority of dean, chair, journal editor-in-chief, professor, and other leadership positions, have the ability to sponsor mid-career academic women, affect career advancement and elevate women to executive leadership positions. [42][43][44] Leadership training programs, such as mid-career leadership seminars, 45 and the Executive Leadership in Academic Medicine 46 have reported that positive benefits such as skills building, increased representation, promotions, retention, and remuneration play a role in promoting gender equity. 38 Sponsors and institutional leaders should support women attending faculty development opportunities and leadership trainings in the mid-career to maintain visibility.…”
Section: Gender Bias Trainingmentioning
confidence: 99%
“…Thus men, who occupy the majority of dean, chair, journal editor-in-chief, professor, and other leadership positions, have the ability to sponsor mid-career academic women, affect career advancement and elevate women to executive leadership positions. [42][43][44] Leadership training programs, such as mid-career leadership seminars, 45 and the Executive Leadership in Academic Medicine 46 have reported that positive benefits such as skills building, increased representation, promotions, retention, and remuneration play a role in promoting gender equity. 38 Sponsors and institutional leaders should support women attending faculty development opportunities and leadership trainings in the mid-career to maintain visibility.…”
Section: Gender Bias Trainingmentioning
confidence: 99%
“…45 Indeed, despite the value in mentorship for those of all genders, including those who identify with underrepresented groups, 40 it may not be sufficient to equitably advance careers. 46,47 Sponsorship, an additive, may be "critical to career advancement." 46…”
Section: Figurementioning
confidence: 99%
“…Our institutions must foster more equitable, diverse, and inclusive environments that support all individuals, especially early career researchers, through formalized policies and access to resources. For example, early career scientists should have access to mentoring systems that make available teams of mentors who reflect and support their personalized career goals and sponsorship by a relevant role model (Gottlieb & Travis, 2018). Scientists at all career stages should be encouraged to use formalized individual development plans as a tool to set goals and facilitate conversations with their mentors (Hobin, Fuhrmann, Lindstaedt, & Clifford, 2012).…”
Section: Recommendationsmentioning
confidence: 99%